Answer:
(-1,1)
Step-by-step explanation:
We take the equation <span>d = -16t^2+12t</span> and subtract d from both sides to get
0<span> = -16t^2+12t - d
We apply the quadratic formula to solve for t. With a = -16, b = 12, c = -d, we have
t = [ -(12) </span><span>± √( 12^2 - 4(-16)(-d) ) ] / [2 * -16]</span>
= [- 12 ± √(144-64d) ] / (-32)
= [- 12 ± √16(9-4d)] / (-32)
= [- 12 ± 4√(9-4d)] / (-32)
= 3/8 ±√(9-4d) / 8
The answer to your question is t = 3/8 ±√(9-4d) / 8
The answer is A trust me I did it before
Answer: ![\bold{\sqrt[4]{2} }](https://tex.z-dn.net/?f=%5Cbold%7B%5Csqrt%5B4%5D%7B2%7D%20%7D)
<u>Step-by-step explanation:</u>
![\dfrac{1}{2}\sqrt[4]{32} =\dfrac{1}{2}\sqrt[4]{2\cdot 2\cdot 2\cdot 2\cdot 2}=\dfrac{1}{2}\cdot 2\sqrt[4]{2}=\boxed{\sqrt[4]{2} }](https://tex.z-dn.net/?f=%5Cdfrac%7B1%7D%7B2%7D%5Csqrt%5B4%5D%7B32%7D%20%3D%5Cdfrac%7B1%7D%7B2%7D%5Csqrt%5B4%5D%7B2%5Ccdot%202%5Ccdot%202%5Ccdot%202%5Ccdot%202%7D%3D%5Cdfrac%7B1%7D%7B2%7D%5Ccdot%202%5Csqrt%5B4%5D%7B2%7D%3D%5Cboxed%7B%5Csqrt%5B4%5D%7B2%7D%20%7D)